Macedonia between nationalism(s) and multiculturalism: The framework agreement and its multicultural conjectures - Atanasov Petar (Sociologija, 2003)
This paper deals with the nationalism(s) and multiculturalism in the Macedonian society, and the multicultural democracy contingency within Macedonian practice. Furthermore, it shed lights on the implementation of the Framework Agreement after the conflict of 2001 seen through the national and multicultural paradigm In addition the paper attempts to correlate the class and the ethnicity in Macedonian socialist pre- ethnic period, with the transition processes and current Macedonian state-of-affairs The paper argues that the management of ethnic differences must reconcile the two nationalisms and in opposite direction, the 'battle' for the resources and symbols between Macedonians and Albanians will reinforce the affections toward their own national (ethnic) identity.